Prevalence and incidence of frailty in Aboriginal Australians, and associations with mortality and disability. (May 2016) - Hyde, Zoë; Flicker, Leon; Smith, Kate; Atkinson, David; Fenner, Stephen; Skeaf, Linda; Malay, Roslyn; Giudice, Dina Lo
Highlights: Frailty has been measured in several ethnic groups, but not in Aboriginal Australians. Frailty in Aboriginal Australians is present at an earlier age than observed in other populations. The prevalence of frailty in remote-living Aboriginal Australians is very high. Frailty of Aboriginal Australians is comparable to that of either a very elderly or institutionalised population. Abstract: Objectives: Frailty represents a loss of homeostasis, markedly increasing the risk of death and disability. Frailty has been measured in several ethnic groups, but not, to our knowledge, in Aboriginal Australians. We aimed to determine the prevalence and incidence of frailty, and associations with mortality and disability, in remote-living Aboriginal people. Study design: Between 2004 and 2006, we recruited 363 Aboriginal people aged ≥45 years from 6 remote communities and one town in the Kimberley region of Western Australia (wave 1). Between 2011 and 2013, 182 surviving participants were followed-up (wave 2). We assessed frailty with an index, comprising 20 health-related items. Participants with ≥4 deficits (frailty index ≥0.2) were considered frail. Disability was assessed by family/carer report. Those unable to do ≥2 of 6 key or instrumental activities of daily living were considered disabled. We investigated associations between frailty, and disability and mortality, with logistic regression and Cox proportional hazards models. Results: At wave 1 (W1), 188 participants (65.3%) were frail, and of robust people at W1 who participated in wave 2, 38 (51.4%) had become frail. Frailty emerged at a younger age than expected. A total of 109 people died (30.0%), of whom 80 (73.4%) were frail at W1. Frailty at W1 was not associated with becoming disabled, but was associated with mortality (HR = 1.9; 95% CI 1.2, 3.0). Conclusions: Frailty in remote-living Aboriginal Australians is highly prevalent; substantially higher than in other populations. Research to understand the underlying causes of frailty in this population, and if possible, reverse frailty, is urgently needed.